2020
DOI: 10.1111/trf.15948
|View full text |Cite
|
Sign up to set email alerts
|

Thawed solvent/detergent‐treated plasma demonstrates comparable clinical efficacy to thawed plasma

Abstract: Background Thawed Plasma (TP), plasma thawed and refrigerated for up to 5 days, is a commonly transfused plasma product. This pilot study was conducted to determine whether Thawed Solvent/Detergent‐treated Plasma stored refrigerated for up to 5‐days post‐thaw (T‐S/D) was as efficacious as TP. Study Design and Methods This single institution retrospective cohort analysis evaluated the efficacy of T‐S/D in reversing coagulopathies in comparison to TP. Utilizing the institution's electronic medical records, trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…There was no difference in mortality, transfusion reactions, readmission rates, length of stay in hospital, and deep venous thrombosis (DVT) incidence between blood products. 56 Mean total dose of octaplasLG (0.52 units [±1.43]) was comparable with that of TP (0.64 units [±1.74]). However, the standardized volume of octaplasLG resulted in a lower transfusion volume required to reverse coagulopathies to the same extent as the higher TP volume, with 126 mL less thawed octaplasLG transfused versus thawed and refrigerated TP ( p = .0001), which could be beneficial for patients at risk of TACO.…”
Section: Octaplas Octaplaslgmentioning
confidence: 81%
See 1 more Smart Citation
“…There was no difference in mortality, transfusion reactions, readmission rates, length of stay in hospital, and deep venous thrombosis (DVT) incidence between blood products. 56 Mean total dose of octaplasLG (0.52 units [±1.43]) was comparable with that of TP (0.64 units [±1.74]). However, the standardized volume of octaplasLG resulted in a lower transfusion volume required to reverse coagulopathies to the same extent as the higher TP volume, with 126 mL less thawed octaplasLG transfused versus thawed and refrigerated TP ( p = .0001), which could be beneficial for patients at risk of TACO.…”
Section: Octaplas Octaplaslgmentioning
confidence: 81%
“…OctaplasLG is currently supplied frozen, and the thawed product is stable during refrigerated storage for ≤5 days. 21,56 However, there is increasing interest in freeze-dried plasma (FDP). 93 Recently, a new freeze-dried form of octaplasLG, octaplasLG powder and solvent for solution for infusion, which upon reconstitution has identical biochemical quality to octaplasLG, 94 has been registered in 17 European countries.…”
Section: Future Directionsmentioning
confidence: 99%
“…There have been several studies evaluating the clinical efficacy of SDP, although the majority have involved relatively few patients and span a broad range of clinical settings 23–33 . Four of these were prospective studies in which patients were randomized to either FFP or SDP, and all showed no significant clinical differences after transfusion of either plasma product 27–30 .…”
Section: Discussionmentioning
confidence: 99%
“…There have been several studies evaluating the clinical efficacy of SDP, although the majority have involved relatively few patients and span a broad range of clinical settings. [23][24][25][26][27][28][29][30][31][32][33] Four of these were prospective studies in which patients were randomized to either FFP or SDP, and all showed no significant clinical differences after transfusion of either plasma product. [27][28][29][30] Five were prospective, observational studies with 8, 24 30, 23 63, 25 67, 31 and 164 26 patients enrolled; these studies again found that SDP was clinically effective, and no significant differences between FFP and SDP were detected.…”
Section: Discussionmentioning
confidence: 99%
“…Racine‐Brzostek et al. (2020) reported that the high temperature generated by MT could exacerbate protein aggregation and denaturation, resulting in higher cooking losses. Similarly, Sun et al.…”
Section: Key Factors Of Thawing Technologies Affecting Muscle Foodsmentioning
confidence: 99%